Urgensi Penyusunan Tes Hasil Belajar: Upaya Menemukan Formulasi Tes Yang Baik dan Benar - Muhammad Rapono; Safrial Safrial; Candra Wijaya (Universitas Negeri Medan, 2019)
Evaluation is a process that includes measurement and may also contain decision making about values. Tests are ways that are used or procedures taken in the framework of measurement and assessment in the field of education, which provides assignments and a series of tasks given by the teacher so that values can be symbolized by students' behavior or achievements. The learning outcomes of each student are compared with the level of achievement of competencies in instructional objectives. There are three things that are important in terms of the test, first is the term measurement. Giving tests (testing is part of measurement activities) Both tests are a tool to measure a sample of knowledge or abilities possessed by a person Third, tests are interpretations of numbers obtained to determine whether a person is good enough or not to learn in achieving a goal. learning or teaching needs to be evaluated in order to know the level of exhaustion of the planned goals so that in the teaching process produces students who have high cognitive, affective and psychomotor aspects and also have an impact on the progress of the nation.